2022
DOI: 10.1186/s12872-022-02758-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the risk factors for myocardial infarction in diet-induced prediabetes: myocardial tissue changes

Abstract: Background Hyperglycaemia is known to result in oxidative stress tissue injury and dysfunction. Interestingly, studies have reported hepatic and renal oxidative stress injury during prediabetes; however, any injury to the myocardium during prediabetes has not been investigated. Hence this study aims to assess changes in the myocardial tissue in an HFHC diet-induced model of prediabetes. Methods Male Sprague Dawley rats were randomly grouped into no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 81 publications
0
3
1
1
Order By: Relevance
“…However, there were no significant differences in the SIRT3 content among the experimental groups, and there were no signs of increased ROS production given by protein carbonylation and nitration. These findings are in contrast with other studies that observed an increase in oxidative stress biomarkers and a decrease in antioxidant enzymes in high-fat high-carbohydrates diet prediabetic-induced Sprague Dawley rats [80]. Overall, our data highlight a higher reliance of fructose/STZ rats on FAO to support the energetic needs of the heart, despite no apparent alterations in glycolysis and mitochondrial dynamics and increased ROS generation.…”
Section: Effect Of Resveratrol-rich Diet On Heart Remodelingcontrasting
confidence: 99%
“…However, there were no significant differences in the SIRT3 content among the experimental groups, and there were no signs of increased ROS production given by protein carbonylation and nitration. These findings are in contrast with other studies that observed an increase in oxidative stress biomarkers and a decrease in antioxidant enzymes in high-fat high-carbohydrates diet prediabetic-induced Sprague Dawley rats [80]. Overall, our data highlight a higher reliance of fructose/STZ rats on FAO to support the energetic needs of the heart, despite no apparent alterations in glycolysis and mitochondrial dynamics and increased ROS generation.…”
Section: Effect Of Resveratrol-rich Diet On Heart Remodelingcontrasting
confidence: 99%
“…Impaired glucose homeostasis plays a role in CVD through inflammation, atherosclerosis, endothelial dysfunction, and hypertension [133]. Studies have demonstrated that during prediabetes, there is an increase in heart rate, blood pressure, CRP, and ET-1 and a decrease in eNOS; therefore, there is an increased risk of MI [134]. Impaired fasting glucose (IFG) is associated with unrecognized myocardial infarctions in a multi-ethnic population free of baseline cardiovascular disease [135].…”
Section: Prediabetesmentioning
confidence: 99%
“…There is growing evidence that respiratory disorders may also be associated with prediabetes ( 11 13 ). While the primary focus has traditionally been on the risk of cardiovascular disease and microvascular complications in prediabetes, attention should also be increased to the potential impact on pulmonary health ( 85 ). See in Figure 2 below.…”
Section: Overview Of Pulmonary Fibrosismentioning
confidence: 99%
“…Prediabetes is a metabolic condition that serves as an intermediate stage in the progression from normal glucose metabolism to overt diabetes and is associated with an increased risk of developing T2DM and cardiovascular disease ( 85 , 86 ). This intermediate hyperglycemic state is characterized by impaired glucose tolerance and elevated blood sugar levels below the threshold for diabetes diagnosis ( 86 ).…”
Section: Prediabetesmentioning
confidence: 99%